FEATURES OF THE MICROBIOME OF THE UPPER RESPIRATORY TRACT IN CHILDREN WITH RECURRENT RESPIRATORY DISEASES - A. V. Shabaldin; E. V. Shabaldina; A. S. Simbirtsev (Инфекция и иммунитет, 2018)
Studies of the metagenome of the upper respiratory tract in children showed the presence of five major bacterial phyla: Proteobacteria, Firmicutes, Bacteroidetes, Actinobacteria and Fusobacteria. Were revealed population differences in the distribution of weights of the above listed phyla, but subject to the dominance of the Firmicutes. Proved the role of environmental factors and time of year for representation in these biotopes of the phyla: Firmicutes, Proteobacteria, Bacteroidetes. Recurrent respiratory infections, hypertrophy of the tonsils of the lymphoid pharyngeal ring, secretory middle ear infections in children is associated with carriage of Haemophilus (H.) parainfluenzae, H. paraphrohaemolyticus, Gemella (G.) haemolysans, G. morbillorum, G. sanguinis, Streptococcus (S.) pneumoniae, S. pseudopneumoniae, S. intermedius, S. agalactiae.